ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF THE LEAF EXTRACTS OF EUCALYPTUS GLOBULUS - Abirami, Subramanian; Nishanthini, Kannan; Poonkothai, Mani (International Journal of Current Pharmaceutical Research, 2017)
Objective: To investigate the antimicrobial activity and phytochemical analysis of Eucalyptus globulus leaves. Methods: The antimicrobial activity of the leaves of E. globulus extracted with acetone, ethanol and petroleum ether was studied using well diffusion method against the selected bacterial and fungal isolates. The antimicrobial susceptibility of the bacteria and fungi to various concentrations of the extract was evaluated by the micro broth dilution method. The preliminary phytochemical screening was performed in the acetone extract of E. globulus. The presence of functional groups in the acetone extract of the leaves of E. globulus was determined by Fourier to transform infrared (FT-IR) spectroscopy. Results: Results suggested that the acetone extract exhibited maximum antimicrobial activity against the tested bacteria and fungi when compared with ciprofloxacin and fluconazole respectively (standard antibiotics). Minimum inhibitory concentration (MIC) showed that the wells containing a concentration of 12.5 mg/ml and 6.25 mg/ml of acetone extract inhibited the bacteria and fungi effectively. Phytochemical screening of acetone extract of E. globulus showed the presence of alkaloids, flavonoids, phenols, tannins, quinones, glycosides, steroids, terpenoids and leucoanthocyanides. FT-IR spectral analysis of the leaf extract of E. globulus showed the presence of functional groups such as–OH,-NH, C=O and–COOH. Conclusion: Thus to conclude, different plants and their formulations have been used in ayurveda to cure diseases for several decades. The findings of the study indicate the potential to exploit the leaves of Eucalyptus globulus in the treatment of microbial diseases.